Ethnicity, religious affiliation and girl-child marriage: a cross-sectional study of nationally representative sample of female adolescents in Nigeria - Jacob Wale Mobolaji; Adesegun O. Fatusi; Sunday A. Adedini (BMC, 2020)
Abstract Background The persistently high prevalence of girl-child marriage remains a public health and developmental concern in Nigeria. Despite global campaign against the practice and policy efforts by Nigerian government, the prevalence remains unabated. This study investigates the prevalence and the influence of ethnicity and religious affiliation on the girl-child marriage among female adolescents in Nigeria. Methods Data of 7804 girls aged 15-19 years extracted from the 2013 Nigeria Demographic and Health Survey were used. Ethnic groups were classified into five: major Northern ethnic group (Hausa/Fulani); Northern ethnic minorities; two major Southern ethnic groups (Yoruba and Igbo), and Southern ethnic minorities. The prevalence of girl-child marriage was determined for the five ethnic groups and individually for each ethnic minority group. Relationships between ethnicity and religious affiliation on girl-child marriage were explored using Cox proportional hazard regression models, adjusting for residence, education and wealth quintile. Results Child marriage was higher for the Northern majority ethnic group of Hausa/Fulani (54.8%) compared to the two major Southern ethnic groups (3.0-3.6%) and aggregated Northern ethnic minorities (25.7%) and Southern minorities (5.9%). However, overall, the less known Northern ethnic minority groups of Kambari (74.9%) and Fulfude (73.8%) recorded the highest prevalence. Compared to the major Southern ethnic group of Yoruba, the adjusted hazard ratio (AHR) of child marriage was significantly higher for Northern ethnic minorities (AHR = 2.50; 95% C.I. = 1.59-3.95) and Northern major ethnicity (AHR = 3.67, 95% C.I. = 2.33-5.77). No significant difference was recorded among Southern ethnic groups. Girls affiliated to other religions (Muslim and traditionalist) had higher child-marriage risks compared to Christians (AHR = 2.10; 95% C.I. = 1.54-2.86). Conclusion Ethnicity and religion have independent associations with girl-child marriage in Nigeria; interventions must address culturally-laden social norms that vary by ethnic groups as well as religious-related beliefs.